Mobile Adventure: RIAMOS to Strengthen the Development of Mathematical Logic and Language in Early Education in Rural Contexts - Rodríguez , Diana Isabel Rodríguez; Quichimbo , Danilo Marcelo Diaz; Dután, David Eduardo Guillén; Correa , Ximena Patricia Curay (Journal of Ecohumanism, 2024)
In the development of the substantive function of the link with society of the National University of Education (UNAE), the Mobile Adventure: RIAMOS project arises from the career of Early Childhood Education (EI), with the aim of building experiential learning experiences, from educational contexts that promote the comprehensive training of children in early childhood in rural contexts. Therefore, this research analyses the impact of Aventura Móvil: RIAMOS on the development of the areas of logical-mathematical relations, comprehension and expression of language in early education in rural contexts. We worked with a methodology based on a mixed approach, with a prevalence of a qualitative, descriptive and interpretative approach and a quantitative approach focused on the pre- and post-tests applied to children in rural parishes in Cañar and Azuay. Mobile Adventure: RIAMOS is a space that integrates different actors: students, parents, authorities, teachers, students in training for comprehensive education. Through the pre-test, educational needs were identified, which were strengthened throughout the class sessions through the implementation of innovative planning, relevant to reality. The post-test reflected the advances and progress made by each child with the application of the didactic strategies and activities. In summary, Mobile Adventure: RIAMOS proves to be an effective initiative to enhance the reinforcement and integral learning of children in rural environments.